The burden on public emergency departments during the economic crisis years in Greece: a two-center comparative study. (February 2019) - Koutserimpas, C.; Agouridakis, P.; Velimezis, G.; Papagiannakis, G.; Keramidis, I.; Ioannidis, A.; Samonis, G.
Abstract: Objectives: The effects of the Greek economic crisis on the emergency departments (EDs) of public hospitals have not been evaluated. The study aims to evaluate the burden of the financial crisis on public hospital's EDs. Study design: The present study is a retrospective two-center comparative study. Methods: ED visits, related admissions per year, and the admissions/visits ratio at two public Greek hospitals, the Sismanogleio of Athens (SHA) and the University Hospital of Crete (UHC), from 2008 to 2016 were retrospectively studied. A linear model was fitted for each variable, and the slope values of the linear equations were calculated and compared between the two institutions. Results: ED visits of the UHC exhibited 8.9% increase during the study period, whereas related admissions and admissions/visits ratio increased by 23.4% and 12.5%, respectively. ED visits at the SHA exhibited 5.4% increase, whereas related admissions showed 6% decrease and the admissions/visits ratio was decreased by 8%. Significant differences between the rates of admissions ( P  < 0.001) and admissions/visits ratio ( P  = 0.001) among the two hospitals were observed. Conclusions: Both institutions showed similarly increased ED visits. However, the UHC serving mainly rural, but also suburban and urban population, exhibited different changes regarding admissions and admissions/visits ratio compared with the SHA serving mainly an urban and suburban one, reflecting the way the crisis affected each social group. Depression has amplified the Greek National Health System structural problems and exposed the problematic urban primary health care. Improvement of primary urban health care, autonomy of EDs, and establishment of emergency medicine as independent specialty in Greece could serve better patients seeking care in public hospitals' EDs. Highlights: Since 2009, Greece is undergoing a severe economic recession. The present study is the first study evaluating crisis' effects in emergency departments. Different populations lead to different changes. This reflects the way the crisis affected each geographical area and social group. We propose solutions for Greece and for other countries facing similar issues.